Creating Collaborative Learning Environment for Quality Education - Pandey, Shiv Ram (Journal of Social Work and Science Education, 2025)
This review article is on ‘Creating Collaborative Learning Environment for Quality Education’. The methods and techniques that were used in this study are document review and reviewing related theoretical knowledge. Relevant literature has been reviewed to make the study conceptually and theoretically reliable and authentic. The study is based on secondary sources. The study explores theoretical ideas on collaborative learning and how and why teachers create collaborative learning environment in their classroom. The crux of collaborative learning lies in this conviction of the potency of teamwork and collective effort and intelligence. Collaborative learning presents a multitude of advantages and holds the capacity to revolutionize the contemporary education system. Educators can amplify and magnify student engagement and ameliorate learning outcomes greatly by implementing technological competencies.